(untitled) (Research, Society and Development, 2024)
The article addresses the history of vaccinations in Brazil, from the creation of the National Immunization Program to the challenges currently faced related to the dissemination of fake news. Objective: To analyze the damage caused to public health by the dissemination and sharing of untrue information in the media and how this can bring to light new outbreaks of diseases that have already been eradicated. Methodology: This article consists of an integrative review and analysis of articles. To compose the study, scientific productions that dealt with the topic in question were selected, with the same bias, for this it was necessary to search for articles published over a period of five years, in Portuguese and with the use of health descriptors: vaccination, immunization, public health and misinformation. Results: 61 published articles were found, the articles were read and analyzed, leaving 11 that fit the research theme. Final considerations: Given the facts presented, it is clear that fake news and conspiracy theories shared on social media are seen as a major challenge to be faced in technological society, as it has a great potential to negatively influence the favor of non-vaccination.